Penegakan Hukum Tindak Pidana Kekerasan Fisik: Studi Kasus Leon Dazon dalam Perspektif Undang-Undang No.1 Tahun 2023 - Isri Al Iqna Saputri; Hana Faridah (Jurnal Hukum Lex Generalis, 2025)
Dating violence is a phenomenon that is increasingly receiving attention in Indonesia, especially with the increasing number of cases involving public figures or the public. This study analyzes law enforcement against physical violence in dating relationships, focusing on a case involving actor Leon Dozan. Leon is suspected of committing violence against his girlfriend, Rinoa Najwa Aurora, twice in September and November 2023, triggered by an iPhone. This case is explained based on Article 466 paragraph (1) of the new Criminal Code which regulates physical violence that results in pain or injury. This study uses a qualitative approach with a case study method, data collection from legal documentation, and media analysis. The results of the study indicate that although the legislation has been updated, there are still challenges in law enforcement, including public perception of dating violence and inconsistent application of the law. These findings are in line with previous studies that highlight the complexity of dating violence among adolescents and students. This study recommends increasing the socialization of the new Criminal Code and training for law enforcement officers to ensure better protection for victims of dating violence.